1990
DOI: 10.1177/030089169007600106
|View full text |Cite
|
Sign up to set email alerts
|

Hormones in Male Breast Cancer

Abstract: Urinary levels of testosterone, 5 alpha-androstanediol, 17-hydroxycorticosteroids, pregnanediol, and circulating levels of testosterone, 17 beta-estradiol, dehydroepiandrosterone-sulfate, prolactin, luteinizing hormone, follicle-stimulating hormone and sex hormone-binding globulin, were measured in 10 male patients with breast cancer and in a suitable group of healthy controls. No difference, either in blood or in urine, was observed between the two groups in the hormonal levels. The lack of abnormalities in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…There are case reports of men who have developed breast cancer after estrogen treatment of prostate cancer. 18 Studies relating levels of estrogen as well as obesity in male breast cancer patients and matched controls have not been consistent; 19,20 but, appear to increase risk. Other etiologic factors in male breast cancer include occupational hazards such as chronic heat exposure, which suppresses testicular function.…”
Section: Discussionmentioning
confidence: 99%
“…There are case reports of men who have developed breast cancer after estrogen treatment of prostate cancer. 18 Studies relating levels of estrogen as well as obesity in male breast cancer patients and matched controls have not been consistent; 19,20 but, appear to increase risk. Other etiologic factors in male breast cancer include occupational hazards such as chronic heat exposure, which suppresses testicular function.…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal imbalance between oestrogen (excess) and testosterone (deficiency) has been suggested as a possible mechanism of MBC though male patients do not have detectable hormonal imbalances [13][14][15]. This imbalance may occur endogenously due to testicular maldescent, injury, mumps orchitis [16] or cirrhosis of the liver [17,18] or by increased peripheral aromatisation of androgens.…”
Section: Aetiologymentioning
confidence: 99%
“…In terms of aetiological mechanisms, high oestrogen levels have been reported as a risk factor for male breast cancer (Sasco et al, 1993), and various studies have found higher serum or urinary oestrogen levels in cases than in controls, but not all results were consistent (Calabresi et al, 1976;Ribeiro et al, 1980;Nirmul et al, 1982;Casagrande et al, 1988;Ballerini et al, 1990;Olsson et al, 1990).…”
mentioning
confidence: 99%